2013
DOI: 10.3233/wor-121503
|View full text |Cite
|
Sign up to set email alerts
|

Students' description of factors contributing to a meaningful clinical experience in entry-level physical therapist professional education

Abstract: OBJECTIVE:The objective of this study was to identify student, clinical instructor (CI), and environmental characteristics and behaviors that make for positive clinical experiences as perceived by physical therapy students. PARTICIPANTS: Nine third-year physical therapist students from entry-level physial therapist education programs around the United States participated in this study. METHODS:In this phenomenologic study, participants were interviewed using open-ended questions designed to facilitate rich des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…Studies were from the USA, [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Australia, 14,[35][36][37][38][39][40][41][42][43] Canada, 28,[44][45][46][47][48] the UK, [49][50][51][52] South Africa 53 and Nigeria. 54 Professions represented included physiotherapy, 15,19,21,27,29,31,33,36,38,45,…”
Section: Resultsmentioning
confidence: 99%
“…Studies were from the USA, [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Australia, 14,[35][36][37][38][39][40][41][42][43] Canada, 28,[44][45][46][47][48] the UK, [49][50][51][52] South Africa 53 and Nigeria. 54 Professions represented included physiotherapy, 15,19,21,27,29,31,33,36,38,45,…”
Section: Resultsmentioning
confidence: 99%
“…The experience creation scale captures CIs’ ability to create LExps across a variety of student learning styles and abilities. In prior studies, students reported that CIs who take the time to get to know the student’s preferred learning style, respond to the student’s individual learning needs, engage the student as an adult learner, and use multiple types of instructional strategies create an effective LExp [ 4 , 12 , 13 ]. Additionally, the PT literature has identified essential CI characteristics as including goal setting and goal writing, as well as teaching and learning styles [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study provides some insight into learners' preparedness to transition from academic to clinical learning by identifying three major components of HBO (site, unit/service & individual). Work readiness dimensions of work competence (knowledge and skills) [11][12][13][14]15,[21][22][23] and personal characteristics 15,16 have been explored in studies, however, we could not find studies detailing the organizational acumen dimension (knowledge of the area, procedures, and policies) and its relationship to learner preparedness. Our findings suggest that opportunities to develop specific organizational acumen during HBO could play an important factor in helping learners feel prepared transitioning between academic and clinical learning.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14] Interestingly, and perhaps in slight contrast to the training as orientation mentioned above, rehabilitation sciences preceptors and learners e64 (occupational therapy, physiotherapy, and speechlanguage pathology) identify the learners' personal attributes and interpersonal skills -such as willingness, professionalism, communication and interaction, and personal attributes and skills, as key indicators of preparedness for clinical learning. 15,16 In a study of recent nursing graduates, medical learners, and organizational representatives, four dimensions of work readiness ('the extent to which graduates possess the attributes that prepare them for success in the workplace') were identified: work competence, personal characteristics, social intelligence, and organizational acumen. 17 For us, the organizational acumen dimension in particular could be a useful lens to understand how HBO prepares learners to successfully transition from academic to clinical learning.…”
Section: Introductionmentioning
confidence: 99%